Terapi Kognitif Perilaku Untuk Pasien Voyourisme: Laporan Kasus Berbasis Bukti Cognitive Behavior Therapy For Voyourisme: An Evidence Based Case Report - Gunawan, Hendra; Nugroho , IGB Indro; Kusuma , Wijaya (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
The problem of sexual deviance has become a social problem among the people. Several forms of sexual deviance include sexual development which results in type identity disorder, paraphilia, psychosexual dysfunction and others. voyourism becomes sexually aroused by watching an unsuspecting person undress, get naked or have sex, voyourism disorder involves voyouristic urges or fantasies or is distressed by or unable to function because of these urges. This study aims to determine the effectiveness of Cognitive Behavior Therapy to reduce symptoms in patients with Voyourism. The search method is carried out from trusted journal sources and is often used to search for scientific journals, including PubMed, Cochrane, MedlinePlus, Proquest, and Science Direct. The keywords used are